2020
DOI: 10.1007/s00423-020-02006-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between gastric Candida colonization and surgical site infections after high-level hepatobiliary pancreatic surgeries: the results of prospective observational study

Abstract: Aim High-level hepatobiliary pancreatic (HBP) surgeries are highly associated with surgical site infections (SSIs), in which microorganisms have a significant role. In the present study, we investigated whether gastric Candida colonization had a significant role in SSIs after high-level HBP surgeries. Methods Between May 2016 and February 2017, the 66 patients who underwent high-level HBP surgeries were enrolled in the present study. The gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A study on high-level hepato-biliary-pancreatic surgery demonstrated a relationship between the colonization of the gastric juice by Candida spp. and postoperative SSI [22]. In that study, colonization of the gastric juice by Candida spp.…”
Section: Discussionmentioning
confidence: 88%
“…A study on high-level hepato-biliary-pancreatic surgery demonstrated a relationship between the colonization of the gastric juice by Candida spp. and postoperative SSI [22]. In that study, colonization of the gastric juice by Candida spp.…”
Section: Discussionmentioning
confidence: 88%
“…We routinely used cefmetazole, which had the antimicrobial coverage of Klebsiella species, in contrast to first-generation cephalosporin. In addition to bacterial pathogens, some articles addressed that Candida species in bile were a significant factor in developing IAA [ 29 , 30 ]. It was considered that the fungal infection process not only caused physical damage to organ walls, allowing other microorganisms to penetrate more easily, but also directly stimulated the bacterial growth (synergetic ability of fungal–bacterial coinfection) [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%